2020
DOI: 10.1101/2020.02.14.948299
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heterotrophic Carbon Fixation in a Salamander-Alga Symbiosis

Abstract: The unique symbiosis between a vertebrate salamander, Ambystoma maculatum, and unicellular green alga, Oophila amblystomatis, involves multiple modes of interaction. These include an ectosymbiotic interaction where the alga colonizes the egg capsule, and an intracellular interaction where the alga enters tissues and cells of the salamander. One common interaction in mutualist photosymbioses is the transfer of photosynthate from the algal symbiont to the host animal. In the A. maculatum-O. amblystomatis interac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Oophila within the capsular chamber provide an increase in the partial pressure of oxygen during the day, potentially remove nitrogenous waste, and have been reported to transfer photosynthate to the amphibian embryos (Bachmann et al 1986;Goff and Stein 1978;Graham et al 2013;Kerney 2011;Pinder and Friet 1994), which may lead to acceleration of embryonal development, larger sized embryos, increased viability and hatching success (Gilbert 1942(Gilbert , 1944. However, other studies have reported no measurable exchange of photosynthate from algae to amphibian embryos (Burns et al 2020). Additional effects by the algae, such as a reduction of micro-organisms that are potentially harmful to the host, have been hypothesized (Kim et al 2014) but not yet tested.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oophila within the capsular chamber provide an increase in the partial pressure of oxygen during the day, potentially remove nitrogenous waste, and have been reported to transfer photosynthate to the amphibian embryos (Bachmann et al 1986;Goff and Stein 1978;Graham et al 2013;Kerney 2011;Pinder and Friet 1994), which may lead to acceleration of embryonal development, larger sized embryos, increased viability and hatching success (Gilbert 1942(Gilbert , 1944. However, other studies have reported no measurable exchange of photosynthate from algae to amphibian embryos (Burns et al 2020). Additional effects by the algae, such as a reduction of micro-organisms that are potentially harmful to the host, have been hypothesized (Kim et al 2014) but not yet tested.…”
Section: Introductionmentioning
confidence: 99%
“…Isolates of this clade have been consistently considered as O. amblystomatis, which is regarded as the numerically most abundant alga in A. maculatum (Jurga et al 2020) and A. gracile (Kerney et al 2019;Marco and Blaustein 2000) egg capsule chambers. These O. amblystomatis isolates have been used in studies of gene expression (Burns et al 2017;Kerney et al 2019), carbon fixation (Burns et al 2020), and host-symbiont fidelity (Kerney et al 2019). As an exception, a few isolates from A. maculatum egg masses, along with environmental samples, were assigned to Chlamydomonas gloeophila; however, C. gloeophila was suggested to represent low abundance green algae occurring in these egg masses that outcompeted Oophila under agar media growth conditions in culture (Kim et al 2014).…”
Section: Introductionmentioning
confidence: 99%